Assessment and prospects of protective forest planting in the North-Western Caucasus - M. D. Shekhmirzova; N. A. Trusheva; N. R. Brzhetseva (Новые технологии)
The article is devoted to the current state of the protective forest plantations in the North-West Caucasus, the history of their creation and relevance in the national economy of the region of research. The issues of arrangement, design, breed composition of protective belts, the effectiveness of their use have been covered. At present, measures are needed in the North-West Caucasus to improve and ensure a qualitative change of generations of plantings, reconstruction of forest shelter belts, and therefore the issues under consideration are relevant. The research has revealed the current state, species composition, design of protective forest plantings in the Republic of Adygeya. Common oak, green ash, Tatarian maple, Amur maple are considered to be main forest-forming species. A brief ecological and biological characteristic of black walnut is given as a promising introduced species for field-protective forestation. Marked design - Open planted and permeable constructions are marked. In order to preserve soil fertility in the future, it is necessary to restore and construct new protective forest belts.